Analisa kepastian hukum terhadap kepemilikan unit rumah susun yang belum memperoleh sertifikat hak milik - Meike Binsneyder; Nynda Fatmawati Octarina (University of Merdeka Malang, 2022)
Along with the increasing need for residents to find jobs that provide better income in the city, this has had an impact on increasing the need for housing. On the one hand, the availability of affordable land and housing is a problem for the urban population explosion. For this reason, the effort to build flats is a priority for housing procurement, considering the large number of residents who need a place to live. With consideration of affordable prices, the construction of flats for middle-class residents while still paying attention to the standardization of decent, healthy, and comfortable housing. Law No. 20 of 2011 concerning Flats (UU Rumah Susun) in Article 24 explains that the construction of flats must comply with technical and administrative provisions and UUPK concerning the rights of residents buying flats to obtain a certificate which must be fulfilled according to the agreed agreement. The problem that occurs is that in fact, the flats are commercial in nature, both in the form of flats and apartments in several areas, many of which the owners have not yet obtained a certificate of ownership of the flats. With regard to this fact, after the flats are sold and bought by the public, the buyer is entitled to the part that has been sold, and the developer cannot own it.How to cite item: Binsneyder, M., Octarina, N. (2022). Analisa kepastian hukum terhadap kepemilikan unit rumah susun yang belum memperoleh sertifikat hak milik. Jurnal Cakrawala Hukum, 13(1), 38-48. DOI:https://doi.org/10.26905/idjch.v13i1.5623.